The Evolution and Antecedents of Transformational Advertising: A Conceptual Model - VANITHA, Swaminathan (Institutional Knowledge at Singapore Management University, 1996)
Transformational advertising provides a key concept for explaining consumers' reactions to advertising. The Product Life Cycle literature suggests that advertising evolves as product-markets develop. The consumer learning perspective suggests that consumers also evolve as markets mature. This suggests that consumers' information needs change with the passage of time. The antecedents of transformational advertising are identified, and an overall model is created to predict the likelihood of transformational advertising. Among the proposed predictor variables are consumer factors (e.g., involvement, conspicuousness) and market factors (e.g., product homogeneity, technological stability). The framework presented here furthers our understanding of the relationship between consumer behavior and advertising trends.